On the genus Calyptobates Polhemus & Polhemus (Hemiptera: Heteroptera: Gerridae) from India with description of a new species and a key to the species of World - Jehamalar, E. Eyarin; Chandra, Kailash (Zootaxa, 2014)
Calyptobates rajani sp. nov. is described from Great Nicobar Island, Andaman and Nicobar Islands, India. This new species is closely related to C. andaman Polhemus & Polhemus, 1994, described from Andaman Islands, India. Two species of Calyptobates Polhemus & Polhemus including the new species are presently known from India. A key to the species of Calyptobates from world and the distribution map of Indian species are also provided.